جناس الاشتقاق في القرآن الكريم: دراسة تحليلية بلاغية في سورة الطور - Moh. Sahlan; Wan Azura Wan Ahmad (NUN Gemilang Enterprise, 2024)
This study intends to explain jinās al-ishtiqāq as viewed by scholars of balagh, identify and analyse the verses containing jinās al-ishtiqāq in surat Al-Tur, and dwell on its portrayal (al-mumāthil and al-mughāyir) in the surat besides explaining its rhetoric and philological significances. This study adopts two methods, i.e. deductive method to draw information from its sources, and analytical method in analysing and interpreting the Qur’anic verses in terms of rhetoric significance. To sum up, this study reveals that jinās al-ishtiqāq al-mughayir is more frequent than jinās al-ishtiqāq al-mumāthil. The study of jinās al-ishtiqāq al-mumāthil allows the possibility and emphasis of meaning whereas jinās al-ishtiqāq al-mughayir that allows the reinforcement of verb with masdar and becomes mafcul mutlaq in inflection provides expansion on explanation and elaboration, binding to punctuation requirements. This jinas creates a strong semantic tie between the words, the coherence of text and context, balanced phonetics, and it attracts the audience and listener to the Qur’an.